A survey on the use of mobile phones of the University of the Philippines Diliman students for library and academic purposes - Tomalon, Thaddeus H. Jr.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2008)
The mobile phone being the most ubiquitous technological device has been the subject of many studies in different areas of the academic realm. Its function as a communication tool has been applauded since it started. There are members of the academic community who nod at the use of mobile phones during school hours. Yet it is not surprising that students will find ways of utilizing this innovation in unexpected ways.
This research sought to find out the level of mobile phone technology that is being utilized by UP Diliman students today and how they apply that technology to library and academic use. 155 survey questionnaires have been answered. The responses show that a lot of students of UP Diliman are actually using their cellphones for library use. Most of those who do, take pictures of library materials instead of photocopying those. 41 of the respondents say they use their cellphones to go to online search engines. And even though cellphones are not allowed in most examinations, it is surprising to see that half of the students of UP Diliman have used their mobile phones as a calculator during an examination. And majority of the students have contacted their professors via SMS and have received class suspension notification through the same service. There is also a heavy use of mobile phone organizers among students of UP Diliman. But surprisingly, only a few students have used their mobile phones to download electronic resources from the library. And none of the respondents have contacted a reference librarian nor have accessed the university library's online public access catalog (OPAC) using their mobile phones.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman -- Students; Moblie communication systems; Cellular telephone systems